A Journey of Discovery: SoTL in Physician Assistant Education. (September 2014) - Kelly, Patricia J.
Abstract : This chapter is a description of the utilization of SoTL concepts and Brookfield's Critical Incident Questionnaire in an evidence‐based medicine course in physician assistant education.